Plan estratégico para la comercializadora importadora Coimfagi Cia. Ltda. de la ciudad de Loja, periodo 2016- 2021 - Armijos Hurtado, Julissa Patricia (2017)
The purpose of this paper was to propose the "strategic plan for the importing company COIMFAGI Cía. Ltda. Of the city of Loja, period 2016-2021 ". For this, it was necessary to establish a methodology and information gathering techniques, with which the 32 employees and a sample of 316 clients of the company could be surveyed, where valuable information was collected that allowed to know their internal situation. With the results obtained I can raise an EFI matrix which allowed, through a weighting of 2.70, to recognize that the company is using its strengths to face its weaknesses, being able to determine the following: the company COIMFAGI has exclusivity in lines, Promotions and prices, differentiating it from the competition. Your staff is currently qualified to perform your activities. In addition, we found lack of training for employees in industrial safety and occupational health. The company has the opportunity to increase its sales (specifically confectionery) on special dates, such as the day of love and friendship, teacher's day, mother's day, child's day, father's day, September fair and Christmas. In the external environment, an analysis of external factors, such as economic, social, political-legal, cultural and technological, was carried out, which allowed us to determine, through a weighting of 2.90, that the company is taking advantage of opportunities, Address their threats in an acceptable manner. Once the internal and external factors were found, the SWOT matrix was developed, which enabled the lifting of the High Impact Matrix in which the strategic objectives were determined. These objectives have been defined, have considered to deal with weaknesses and threats in consensus with the executives of the company seeking their implementation with less resistance. The execution of the proposed plan for 5 years involves an investment of $ 18,898.86. Through the results obtained, conclusions were established for the company, they denote the necessity of the execution of the strategic planning. Therefore it is recommended that managers frequently review strengths, weaknesses, opportunities and threats in order to validate if this proposed strategic plan is met. Also, they are always vigilant of the political and economic situation of the environment with the purpose of adapting the strategies; Establish as an enterprise policy the annual training of personnel in matters necessary to enable them to perform their functions better; Take advantage of the free training provided by SECAP (online) and other state institutions (SRI, ARCSA, FIREFIGHTERS), in order to keep staff trained at the lowest costs.